The Relationship between Salivary IgA and White Oral Lesion in Bedridden Patients - Mustafa Al-Ahma, Basma Ezzat; Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Supa'at, Salwana; Wan Nik, Wan Noor Nazayan; Abdul Qader, Omar Abdul Jabbar; Ardini, Yunita Dewi; Mohd Ibrahim, Mohamad Shafiq; Mohd Jefri, Muhammad Hazim; Alias, Amarul Firdaus (Ektodermal Displazi Grubu, 2021)
Abstract The worldwide increase in the aging population poses tough challenges to the health care community. Indeed, older age has been associated with increased burden of chronic diseases. A decline in the protective functions of the oral mucosa could expose the aging individual to a variety of pathogens and chemicals that enter the oral cavity. The role of mucosal immunity in the defence against pathogens is well established. However, there does not seem to be much research on the relationship between salivary secretory immunoglobulin A (sIgA) and white lesion particularly among geriatric residents of long-term health care. Immunoglobulin A (IgA) is the dominant immunoglobulin isotype on oral mucosal surface where it acts as a first line of defence against microbial invasion. Recent investigations suggest that secretory IgA concentrations vary over the day due to a range of variables including dietary factors, daily mood, and exercise. The aim of this study is to investigate the relationship of sIgA level, and salivary pH with white lesion in bedridden patients. In this study, salivary IgA was determined by ELISA in samples of 34 elderly ( 60-80 years old ) subjects grouped as male and female . Unstimulated saliva was collected, saliva flow, PH, and sIgA concentrations were measured. The results showed that the sIgA concentration was significantly higher in patients with white lesion (536.97±88.63) comparing to those with healthy mucosa (323.79±64.01) , and there is no significant difference of sIgA concentration between male (476.46±145.58) and female (396.83±108.09). We concluded that early detection of oral health problems especially white lesion can be determined by the assessment of the sIgA level. This would reflect the salivary IgA protective mechanism in patients with white lesion problems.